Penerapan Rest API Menggunakan Retrofit Untuk Sistem Informasi Film Berbasis Android (Studi Kasus: Sinopsis Film) - Christhover , Robbie; Sugiyatno , Sugiyatno; Herlawati , Herlawati (Journal of Students‘ Research in Computer Science, 2022)
Looking for film information is something that is often done before watching, but not infrequently many people waste time and money because the films they watch are not what they want, due to the lack of information on the films they want to watch. From this problem, the author proposes an application by implementing Rest Api Using Retrofit for an Android-Based Film Information System so that it can search for film synopsis, by utilizing an open-source API. The result of this research is an application that will provide information on the synopsis of the film you are looking for to watch.